Quantification of the components in commercial essential oil of Eucalyptus globulus labill. by gas chromatography – GC-FID and GC-MS - Anders Apel, Miriam; A.F. Rodrigues, Rodney; Lira Soares, Luiz Alberto; Henriques, Amélia Terezinha (Drug Analytical Research, 2026)
Leaves of Eucalytus globulus Labill are characterized by the presence of essential oil, in which 1,8-cineole is the main component. The oil is used as an expectorant for symptomatic treatment of mild inflammation of the respiratory tract and bronchitis. This work addresses the chemical quantification of the constituents of E. globulus essential oil by gas chromatography. Commercial samples were diluted and analyzes by gas chromatograph coupled to flame ionization detector (GC-FID). The chromatographic separation was performed on a fused silica capillary (LM-20, 30 m x 0.25 mm x 0.25 μm film thickness) column. The proposed GC-FID method has demonstrated to have specificity and high sensitivity. The quantitation by the normalization technique demonstrated to be adequate for the analysis. Thus, the proposed method is effective for the quantification of E. globulus oil constituents, which may help in the quality control of commercial formulations.